Financing Sustainable Development : Ideas for Action - Mohieldin, Mahmoud (World Bank, Washington, DC, 2015)
In 2015, global leaders aspire to adopt the Sustainable Development Goals, a financing framework to support them, and a framework agreement on climate change. Youth engagement throughout the design and implementation process is critical for success. World Bank Group and Wharton Business School jointly launched a youth finance competition in November 2014 to engage young people in creating innovative ideas for financing development in the future. 330 submissions from more than 1,500 youth in 130 countries around the world were received. This publication compiles top six proposals as well as short summaries of the top 20 ideas.